Implementation of Quality Management System ISO 9001:2015 Integrated with Accreditation Standards in SMK 1 Sragi - Armawati, Armawati; Syamwil, Rodia; Florentinus, Totok Sumaryanto (Universitas Negeri Semarang, 2018)
Accreditation and ISO become a benchmark that is used as a school in an effort to ensure the quality of education. In applying of Quality Management System ISO 9001: 2015 can be integrated with accreditation standards. Purpose of this research: (1)the evaluation results of ISO 9001: 2015 implementation integrated with accreditation standards in SMK 1 SragiÂ in terms of Context, input, process, product; and (2) inhibiting and supporting factors for the implementation of ISO 9001: 2015 that are integrated with accreditation standards in SMK 1 Sragi. This research was carried out using the CIPP evaluation model from Stufflebeam. Data collection techniques: questionnaires, interviews, and review ofÂ archive documents. The results showed that : (1) The evaluation results of the ISO 9001: 2015 implementation integrated with accreditation standards in SMK 1 Sragi showed that: the context aspect is categorized quite well with an average of 3.18, the input aspect is categorized quite well with an average of 3.23, the process aspect is categorized quite well with an average of 3.19, the product aspect is categorized quite well with an average of 3.06. (2) The inhibiting factors for the implementation of ISO 9001: 2015 integrated accreditation standards in SMK 1 Sragi are stagnation of mindset for sustainable school progress, lack of literary awareness and lack of understanding of risk management, supporting factors for the implementation of ISO 9001: 2015 integrated accreditation standards in SMK 1 Sragi are top management commitment, role of personal, effective communication, and continous improvement.